INTERKONEKSI PENDIDIKAN PERPUSTAKAAN DALAM MENUMBUHKEMBANGKAN BUDAYA BACA - Muhammad Azam Muttaqin; Kharis Syuhud Mujahada; Muhammad Roihan Daulay; Ali Wardhana Manalu (IAIN Padangsidimpuan, 2020)
This research is based on the problem of researchers' anxiety about the school library being used as a means of information needed as a learning resource that enables educators to improve its quality, it is not running optimally. This study aims to look at management, strategy, service optimization, and the form of integration of library management interconnections in an effort to increase reading interest.This type of research is a type of qualitative research with inductive deductive methods, this type of qualitative research is a type of research based on the philosophy of post-positivism. Data collection techniques were carried out by means of observation, interviews, documentation, and questionnaires. The validity of the data was tested by means of a credibility test with technical triangulation, source triangulation, and time triangulation. The results showed: 1) library management which is carried out by the existence of disposable planning and fixed plans, procurement of library materials, management and maintenance and service improvement, 2) strategies to increase students' reading interest are carried out by completing and adding to book collections, providing teaching media, conducting library learning, motivating students with slogan posters and direct invitations, 3) actions in optimizing library service functions by carrying out and implementing properly the functions of educational, informative, recreational, research, and administrative responsibility functions in a library, 4) to determine the form library management interconnection integration.Â